Motif Diri dan Pengelolaan Kesan Jamaah Persatuan Islam Kota Bandung dalam Dakwah dan Politik - Hamzah - Turmudi (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2020)
This study seeks to analyze self-motives and the management of the Islamic Unity congregation's impression in Bandung, both as preachers and politicians. The research was conducted with a qualitative approach through dramaturgical studies that tried to explore the religious understanding of the Islamic Union organization in the political field. The results showed that the self-motive to become a da'i and a politician for the Persis congregation was based on religious understanding from the Persis organization's perspective, which maps the constitutional field as a space for jihad. The motive for becoming a da'i and a politician is also based on the Persis tajdid organization's spirit since the organization's emergence. Meanwhile, the management of impression both as a preacher and politician refers to the view and assessment that politics is a way of da'wah, and da'wah is a political spirit.Keywords: self-motive Impression Management; Da'wah and Politics; Islamic Unity.Penelitian ini berupaya menganalisis motif diri dan pengelolaan kesan jamaah Persatuan Islam di Kota Bandung baik sebagai da’i maupun politikus. Penelitian dilakukan dengan pendekatan kualitatif melalui studi dramaturgis yang berupaya menggali refleksi paham keagamaan organisasi Persatuan Islam dalam bidang politik. Hasil penelitian menunjukkan bahwa motif diri menjadi da’i dan politikus bagi jamaah Persis didasarkan pada paham keagamaan dalam sudut pandang organisasi Persis yang memetakan lapangan konstitusional sebagai ruang jihad. Motif diri menjadi da’i dan politikus juga didasarkan pada spirit tajdid organisasi Persis yang melekat sejak kemunculan organisasi ini. Sementara itu, pengelolaan kesan baik sebagai da’i maupun politikus merujuk pada pandangan dan penilaian bahwa politik adalah jalan dakwah, dan dakwah adalah spirit politik.Kata Kunci: Motif Diri; Pengelolaan Kesan; Dakwah dan Politik; Persatuan Islam.